Cyber Law Reform from the Perspective of Pancasila: Between Legal Certainty and Social Justice: Reformasi Hukum Siber dari Perspektif Pancasila: antara Kepastian Hukum dan Keadilan Sosial - Kurniawan, Itok Dwi (Talenta Publisher, 2025)
This article explores the reform of cyber law in Indonesia from the perspective of Pancasila, emphasizing the tension between legal certainty and social justice. As information technology evolves rapidly, legal challenges in the digital space become increasingly complex, demanding a legal system that is both adaptive and grounded in national foundational values. In this context, Pancasila serves as a normative paradigm guiding legal reform, ensuring that it does not solely prioritize legal certainty but also guarantees the fair protection of citizens' rights. The article analyses various policies and regulations concerning cyber law and examines the extent to which Pancasila principles are reflected in the legislative and implementation processes. Using a normative and conceptual approach, this study aims to contribute to the development of a cyber law framework that is not only responsive to technological change but also embodies social justice for all Indonesians